Sorption experiments with dissolved organic carbon and characterized dust samples from ephemeral rivers in Namibia - Rianne J M van Kaam (PANGAEA, 2025)
Sorption experiments were conducted to investigate the effect of dust deposition in the ocean on the concentration of dissolved organic carbon (DOC). This dataset includes the characterization of dust samples collected from the dry riverbeds of the ephemeral rivers Kuiseb and Omaruru in Namibia in April 2023, as well as the results of the sorption experiments. Dust samples were collected in the form of silt crust from two locations along the Kuiseb River, near the Gobabeb research station and Rooibank, and from one location along the Omaruru River. The samples were gently loosened and sieved through a 63 μm mesh sieve, and only the <63 μm fraction was used for dust characterization and sorption experiments. Two types of sorption experiments were performed. To analyse the release of OC, dust was added to artificial seawater. In addition, time series were performed in which dust was added to a solution of artificial seawater and 13C-labeled Spirulina extract.